UPOLITYCZNIENIE SPORTU W XXI WIEKU NA PRZYKŁADZIE LETNICH IGRZYSK OLIMPIJSKICH - Kobierecki, Michał Marcin (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of the article is to assess the 21st Century Olympic Summer Games from the perspective of their interconnection with politics. The research included Olymics in Athens in 2004, Beijing in 2008, London in 2012 and Rio de Janeiro in 2016. The Games in Beijing have been assessed the most politicized within the analysed period, however each of the sports events have somehow collided with politics. The main research question concerned was whether after the end of the Cold War sport has remained its former political role in international relations.